Therapeutic alliance in individual adult psychotherapy: a systematic review of conceptualizations and measures for face-to-face- and online-psychotherapy - Saxler, Eva; Schindler, Theresa; Philipsen, Alexandra; Schulze, Marcel; Lux, Silke (Frontiers in Psychology, 2024)
Background The therapeutic alliance (TA) is a robust and pantheoretical predictor of treatment outcome in Face-to-Face- (F2F-) and Online-psychotherapy (Online-PT). Many authors have proposed several conceptualizations of TA, which are oftentimes operationalized. The resulting diversity of conceptualizations and measures is presented in this review. Methods We performed a three-parted literature search for self-report-instruments of TA in individual, voluntary F2F-PT with adults (1. utilization of past reviews, 2. systematic literature search yielding 5,205 articles, 3. reference lists). Analogously, we conducted a systematic literature search for instruments of TA in the Online-setting (yielding 200 articles). Additionally, we analyzed the content of the instruments qualitatively. Results A current overview of 48 instruments for measuring TA (46 for F2F-PT, 2 for Online-PT) including their conceptual backgrounds, characteristics and main content aspects is presented. Most instruments (n = 24) operationalize one or more theoretical conceptualizations of TA. Other instruments are adaptation/syntheses of existing measures (n = 14), based on literature searches (n = 3) or on an empirical survey (n = 3) and two instruments provide no conceptual background information. The content of the instruments mainly focused on the following aspects: 1. Self-disclosure and authenticity; 2. Agreement; 3. Active participation, motivation and compliance; 4. Trust and secure attachment; and 5. Considering needs/abilities/wishes of the patient. Additionally, a narrative review of various approaches to conceptualize TA is presented and linked to respective corresponding instruments. Discussion The broad variety of conceptualizations and measures of TA makes coherent research on TA difficult. There are conceptual challenges such as the role of attachment style in TA that remain to be clarified. The current conceptualizations and measures do not incorporate the practical experience and expertise of psychotherapists and patients sufficiently. A metatheoretical conceptualization and measure of TA based on an empirical survey of psychotherapists and patients could address these issues.